Yahoo Web Search

  1. Sort by

  1. Since N is normal bNb^-1 = N ==> aNbN = a(bNb^-1)(bN) = abN(b^-1b)N = abN1N = abN.

    1 Answers · Science & Mathematics · 25/03/2014

  2. Matlab is a standalone software for your computer. You can't use it on the internet. It is a high level programming language used to solve math problems. Although, you can use it for simpler things that a...

    1 Answers · Science & Mathematics · 03/09/2007

  3. Use this site for a final result: http://integrals.wolfram.com/index.jsp

    1 Answers · Science & Mathematics · 21/05/2007

  4. Simply consider the triangle ABN. It is isosceles so AN = BN. We know this because...

    2 Answers · Science & Mathematics · 07/01/2011

  5. ✐Explanation✐ Recall that: y = abⁿ This formula is called Exponential Decay...

    2 Answers · Science & Mathematics · 01/12/2009

  6. Suppose G/N is Abelian. Then, abN = (aN)(bN) = (bN)(aN) = baN So, N...

    1 Answers · Science & Mathematics · 02/04/2009

  7. ...2x^2) (4x) = 32 x cos (2x^2) d/dV [ ( (nRTsin(V)) / 2v ) + abn^2] = [ nRT cos V (2V) - nRT sin V (2) / (2V...

    1 Answers · Science & Mathematics · 16/01/2010

  8. I answered the first problem for you. 1. y = abⁿ Since "a jet ski depreciates at 11% of its original...

    1 Answers · Science & Mathematics · 12/02/2011

  9. ...⁻¹b + nC2 aⁿ⁻²b² + ... + nC(n-1) abⁿ⁻¹ + nCn bⁿ (a+b)ⁿ = Σ(i=0..n) nCi...

    1 Answers · Science & Mathematics · 13/12/2009

  10. ... So... AD + BD + BP + NP = 32 ********** #2: ABN is equilateral, which means each of its angles is...

    1 Answers · Science & Mathematics · 20/12/2007

  1. Try asking your question on Yahoo Answers